2015
DOI: 10.3389/fnagi.2015.00109
|View full text |Cite
|
Sign up to set email alerts
|

Patients with moderate Alzheimer’s disease engage in verbal reminiscence with the support of a computer-aided program: a pilot study

Abstract: This study focused on the assessment of a program recently developed for helping patients with moderate Alzheimer’s disease engage in computer-mediated verbal reminiscence (Lancioni et al., 2014a). Sixteen participants were involved in the study. Six of them used the original program version with the computer showing a virtual partner posing questions and providing attention and guidance. The other 10 used a slightly modified program version with the computer presenting photos and videos and providing encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Studies on small samples show that the introduction of ad-hoc ICT tools could improve the quality of life of older people and increasing the length of time for independent living. Some researchers have investigated new solutions for cognitive assistance in the last three years (serious games and robotic systems) [5][6][7][8][9]. These researches concentrated on exploiting software platforms allowing the support of new assistive tools that are less expensive and more accessible and could be used as a re-education tool helping to slow the decline of people with CI.…”
Section: Motivation and Contextmentioning
confidence: 99%
“…Studies on small samples show that the introduction of ad-hoc ICT tools could improve the quality of life of older people and increasing the length of time for independent living. Some researchers have investigated new solutions for cognitive assistance in the last three years (serious games and robotic systems) [5][6][7][8][9]. These researches concentrated on exploiting software platforms allowing the support of new assistive tools that are less expensive and more accessible and could be used as a re-education tool helping to slow the decline of people with CI.…”
Section: Motivation and Contextmentioning
confidence: 99%
“…The use of a simple computer-aided program to help the participants reminisce events of their life and increase their positive verbal engagement (as pursued in this study) seemed a practical example of such strategy. Participants had expressed their willingness to be involved in the program and staff and families supported it (Lancioni et al, 2015a ). Participants had not been asked to sign a formal consent for their involvement in the study, as they were not considered capable of reading a complex text and/or writing.…”
Section: Studymentioning
confidence: 99%
“…In each of these intervention areas, technology-aided programs were developed and assessed with promising results. For example, Lancioni et al ( 2014b , 2015a ) reported encouraging results with a technology-aided program set up to foster positive verbal engagement/reminiscence in persons with moderate Alzheimer’s disease. The program relied on the presentation of: (a) images of relevant people/events together with requests to talk about them or a virtual partner asking questions; (b) approval for verbal engagement; and (c) reminders (prompts) to seek new images/questions (see also Yasuda et al, 2009 ; Kuwahara et al, 2010 ; Lazar et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations